Impacts of policies and technologies in dryland agriculture: Evidence from northern Ethiopia - Pender, J.L.; Gebremedhin, Berhanu (Crop Science Society of America, 2004)
This chapter investigates the land management practices used in the highlands of Tigray, northern Ethiopia. The factors influencing them, and their implications for crop production. Several factors commonly hypothesized to have a major impact on land management and agricultural production - including population pressure, small landholdings, access to roads and irrigation, and extension and credit programs - are found to have limited direct impact on production, though most affect the intensity of production. The increase in farming intensity due to these factors has limited impact on total crop production due to low marginal product of labor in crop production, limited productivity impact of inputs such as fertilizer in the moisture-stressed environment of Tigray, and limited adoption of such in-puts. We find that profitable opportunities exist to increase agricultural production and achieve more sustainable land management in the highlands of Tigray. These opportunities include improvement of crop production using low-external input investments and practices such as stone terraces, tree planting, manuring, reduced tillage, and reduced burning: and improved livestock management. The comparative advantage of people in the Tigray highlands is not in input-intensive cereal crop production but more in such low-input approaches and in alternative livelihood activities. As a result, greater emphasis on developing these alternatives in agricultural extension and other Development programs may be fruitful. Food crop production should not be ignored in the Development strategy, but less promotion of purchased inputs such as fertilizer and improved seeds and greater emphasis on profitable alternatives would be helpful.